Collaboration Skills: Its Relationship with Cognitive Learning Outcomes in STEM Learning: Keterampilan Kolaborasi: Hubungannya dengan Hasil Belajar Kognitif dalam Pembelajaran IPA Berbasis STEM - Shofiyah, Noly; Wulandari, Fitria Eka; Mauliana, Metatia Intan (Procedia of Social Sciences and Humanities, 2022)
This study aimed to determine the relationship of collaborative skills to cognitive learning outcomes in STEM-based science learning. This correlational study was conducted on science education students at the Muhammadiyah University of Sidoarjo. The research instrument consisted of a questionnaire to assess collaboration skills, as well as an essay test to measure cognitive learning outcomes. Data analysis using person product moment correlation analysis. The results showed that there was a significant relationship between collaboration skills on cognitive learning outcomes with r count (0.425) greater than r table (0.355). Based on the value of r obtained, it can be concluded that collaboration skills have a fairly strong relationship to the learning outcomes obtained by students. Therefore, educators can empower students' collaboration skills, so that students' cognitive learning outcomes also increase.